2017
DOI: 10.1080/20016689.2017.1336044
|View full text |Cite
|
Sign up to set email alerts
|

3. How comprehensive can we be in the economic assessment of vaccines?

Abstract: In two previous papers we argued on current vaccines economic assessment not fully comprehensive when using the incremental cost-utility analysis normally applied for treatments. Many differences exist between vaccines and drug treatments making vaccines economic evaluation more cumbersome. Four challenges overwhelmingly present in vaccines assessment are less important for treatments: requirements for population, societal perspectives, budget impact evaluation, and time focused objectives (control or eliminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The following three elements have helped us in identifying the current list of available methods. First, our internal evaluation comparing treatment with vaccine prevention identified 24 items that could be regrouped into four domains (population focus, societal perspective, budget need, and different role functions of the vaccine over time [6]). This was followed by further investigation on 'budget need' evaluations independent of CEA, such as budget impact analysis (BIA), CBA, CO, and Cobb-Douglas evaluation functions.…”
Section: Available Methods and Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…The following three elements have helped us in identifying the current list of available methods. First, our internal evaluation comparing treatment with vaccine prevention identified 24 items that could be regrouped into four domains (population focus, societal perspective, budget need, and different role functions of the vaccine over time [6]). This was followed by further investigation on 'budget need' evaluations independent of CEA, such as budget impact analysis (BIA), CBA, CO, and Cobb-Douglas evaluation functions.…”
Section: Available Methods and Measuresmentioning
confidence: 99%
“…During the last 15 years, research has identified different stakeholders interested in vaccines and their value assessment [6]. This is reflected in the assessment of factors such as a need for acceptance by the target population (e.g., for HPV vaccination against cervical cancer), or the recognition that much of the benefit of some of the newer vaccines could be seen by nonmedical stakeholders including employers, employees or financial authorities.…”
Section: Stakeholder Types and Their Search For Benefitmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaccination is one of the most cost-effective ways to control and prevent the spread of infectious disease [1]. Pathogens and their metabolites are prepared as an immunological formulation that can be used to prevent or treat infectious diseases by artificial attenuation, detoxification, inactivation, or genetic engineering methods [2].…”
Section: Introductionmentioning
confidence: 99%
“…From 2001 to 2020, the broader benefits could amount to a staggering US$ 820 billion in the 73 countries supported by the Global Alliance for Vaccines and Immunization (GAVI) [2], a public-private partnership (PPP) involving amongst others the UN, the vaccine industry and the Bill and Melinda Gates Foundation (BMGF). Due to the higher disease burden and more limited medical infrastructure, the HE gain from introducing a vaccine in LMICs will be greater than in higher-income countries (HICs), where the gain will largely be determined by competition between the different health options on offer [3].…”
Section: Introductionmentioning
confidence: 99%